REVIEWING THE FATWAS RELATED TO FINTECH APPLICATIONS IN ISLAMIC FINANCIAL INSTITUTIONS IN INDONESIA - Nunung Nurlaela; Muthi Luthfiyana; Andini Sulastri; Evy Sulvy Wahyunita (Share: Jurnal Ekonomi dan Keuangan Islam, 2020)
The tendency of the community towards halal products is currently increasing, not only related to objects/goods but also related to muamalah/interactions. The development of the latest fintech applications needs to be examined and detailed again, to be linked with related sharia law. In addition to examining legal status, an interesting thing to develop is how to formulate a fintech application that is following the Islamic economic perspective. Therefore, it is crucial to always review the National Sharia Board – Indonesian Council of Ulama (Dewan Syariah Nasional – Majelis Ulama Indonesia – DSN-MUI)’s fatwa related to fintech applications in Islamic financial institutions (LKS). The results of this study will be used as input for DSN-MUI to formulate policies and fatwas that is issued. This research is a qualitative type. The research subjects are; (1) Sharia Cards, (2) Sharia Charge Cards, (3) Transfers and Collections, (4) Payment Services, and (5) Sharia Electronic Money. There are differences in the bases for determining the contract of each of these products between Islamic countries. The results of this study indicate that: (1) the sharia card product is more appropriate to use the hawalah contract than the kafalah contract, and it is necessary to fix fines due to maturity, monthly fees that are not related to the amount of debt, and to write off merchant fees; (2) Sharia Charge Card products should use a hawalah contract rather than a kafalah contract and need to eliminate fines due to late payment; (3) the use of the wakalah contract on transfer and collection products is correct; (4) payment service products that use a wakalah and ijarah contract should be sufficient to use one of the two; and (5) electronic money can function as money, with transactions using the hawalah principle, as well as debit cards (wadi'ah principles). So, four improvements are proposed to the DSN-MUI fatwas related to the fintech application.========================================================================================================Tinjauan Terhadap Fatwa Terkait Penerapan Fintech pada Lembaga Keuangan Syariah di Indonesia. Kecenderungan masyarakat terhadap produk-produk halal saat ini semakin meningkat, tidak hanya terkait dengan benda/barang namun juga terkait muamalah/interaksi. Perkembangan aplikasi fintech terbaru perlu dicermati dan didetailkan lagi, untuk dikaitkan dengan hukum syariat terkait. Selain pencermatan status hukum, hal yang menarik untuk dikembangkan adalah bagaimana merumuskan aplikasi fintech yang sesuai dengan pandangan ekonomi Islam. Oleh karena itu sangat perlu untuk selalu meninjau fatwa DSN-MUI terkait aplikasi fintech pada lembaga keuangan syariah (LKS). Hasil kajian ini akan menjadi masukan bagi DSN-MUI untuk merumuskan kebijakan-kebijakan dan fatwa-fatwa yang dikeluarkannya. Penelitian ini berjenis kualitatif. Subjek penelitiannya adalah: (1) Syariah Card, (2) Syariah Charge Card, (3) Transfer dan Inkaso, (4) Jasa Pembayaran, dan (5) Uang Elektronik Syariah. Terdapat perbedaan dasar-dasar penentuan akad dari setiap produk tersebut di antara negeri-negeri Islam. Hasil penelitian ini menunjukkan bahwa: (1) produk syariah card lebih tepat menggunakan akad hawalah dibandingkan dengan akad kafalah, serta perlu membenahi denda akibat jatuh tempo, monthly fee yang  tidak dikaitkan dengan jumlah utang, dan menghapus merchant fee; (2) produk Syariah Charge Card sebaiknya menggunakan akad hawalah dibandingkan dengan akad kafalah serta perlu menghilangkan denda akibat keterlambatan pelunasan; (3) penggunaan akad wakalah pada produk transfer dan inkaso sudah tepat; (4) produk jasa pembayaran yang menggunakan akad wakalah dan ijarah seharusnya cukup menggunakan salah satu dari keduanya; dan (5) uang elektronik dapat berfungsi sebagaimana uang, dengan transaksi menggunakan prinsip hawalah, sebagaimana kartu debit (prinsip wadi’ah). Jadi, diusulkan empat perbaikan atas fatwa–fatwa DSN-MUI terkait aplikasi fintech.